Civil Service in Chile, Analysis of Senior Civil Servants on the Top Rung of the Hierarchy (2003-13) [Serviço Civil No Chile, Análise Dos Diretivos de Primeiro Nível Hierárquico (2003-13)] [Servicio Civil en Chile, Análisis de Los Directivos de Primer Nivel Jerárquico (2003-13)1] - Gonzalez-Bustamante, B (Fundacao Getulio Vargas, 2016)
This article analyses the main factors that affect the election of a high civil servant in the first level of hierarchy in Chile, according to a sociological perspective using the capital species concept. This paper provides a theoretical and descriptive travel on State modernization and professionalization of public management in Chile. Later, with a sample of 45 cases regarding high civil servants designated during the period of 2003-13, a maximum likelihood logit models were performed to determine the factors that influence the selection of these civil servants. It concludes that political capital is not a factor that gives advantage in the selection. © 2016, Fundacao Getulio Vargas. All rights reserved.